Spousal abuse in the assessment of the Dagestan population - Elvira Makhachevna Zagirova (Вестник Майкопского государственного технологического университета)
Violence is one of the destructive social phenomena. It is widespread in any society and has different forms of existence. The greatest attention is drawn to domestic violence, violence against family members (wives, children, elderly parents). The purpose of the research is to establish the attitude of the Dagestan peoples to spousal abuse. The object of the research is domestic violence. The subject of the research is spousal abuse. As a rule, indicators of the measurement of spousal abuse are data on the female subgroup, since it is almost always the victim. The research method is a mass standardized survey. On the basis of the research, it has been found that in the mass consciousness of the Dagestan peoples there is a negative attitude towards spousal abuse and they emphasize its inadmissibility in the family. The author's hypothesis about the key role of education as a factor influencing the family behavior of both men and women has been confirmed by the results of the research. However, the research notes the presence of inconsistency in positions: on the one hand, it emphasizes the inadmissibility of violence in the family, regardless of the circumstances, on the other hand, the focus on its application. Verification of the sociological material shows that in the male subgroup there are fewer people who oppose spousal abuse.